Cherenkov radiation of the relativistic electron bunch in ion dielectric media - Balakirev, V.A.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2019)
The process of wakefields excitation by the relativistic electron bunch in dielectric media with ion type of chemical bond is studied. The spatio-temporal structure of the excited wakefield in ion dielectric waveguide is obtained and investigated. It is shown that the excited wakefield in the infrared and longer wavelength ranges consists of the field of longitudinal optical phonons and Cherenkov radiation as a set of eigen electromagnetic waves of the dielectric waveguide. Досліджено процес збудження Черенківського електромагнітного випромінювання релятивістським електронним згустком в іонному діелектричному хвилеводі. Отримана і досліджена просторово-часова структура кільватерного поля в іонному діелектричному хвилеводі. Показано, що збуджене кільватерне поле в інфрачервоному діапазоні і більших довжинах хвиль складається з поля поздовжніх оптичних фононів і набору власних електромагнітних хвиль діелектричного хвилеводу. Исследован процесс возбуждения Черенковского электромагнитного излучения релятивистским электронным сгустком в ионном диэлектрическом волноводе. Получена и исследована пространственно-временная структура кильватерного поля в ионном диэлектрическом волноводе. Показано, что возбуждаемое кильватерное поле в инфракрасном диапазоне и больших длинах волн состоит из поля продольных оптических фононов и набора собственных электромагнитных волн диэлектрического волновода.